Mechanical and environmental characteristics of red mud geopolymers. (28th February 2022) - Sun, Zengqing; Tang, Qingyu; Xakalashe, Buhle Sinaye; Fan, Xiaohui; Gan, Min; Chen, Xuling; Ji, Zhiyun; Huang, Xiaoxian; Friedrich, Bernd
Highlights: Release of major components, heavy metals and trace elements were characterized. Red mud geopolymers obviously affect chroma and turbidity of water body. Releases of Pb, Sb and V surpass the environmental regulatory limits. Release is controlled by diffusion, with signs of surface wash-off, solubility and depletion. Abstract: Red mud is an industrial waste produced during the bauxite refining in the Bayer process. Increasing efforts have been recently paid to produce red mud geopolymers with feasible engineering properties. Meanwhile, the environmental compatibility of red mud geopolymers as construction material has not been clearly investigated. To facilitate clean production of red mud geopolymers, the release characteristics of Na, K, Al, Si, Ca, B, Ba, As, Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb, Sb, Se, Sr, Tl, V, Zn, Cl − and SO4 2− from red mud geopolymers of different mixture proportions were investigated. Mechanisms dominating the release behaviors were also revealed. Results showed that red mud geopolymers significantly affect the chroma and turbidity of water body. Though the cumulative releases of most of the chemical components are in a similar range as cement-based materials, leaching of Pb, Sb and V in some cases surpass the environmental regulatory limits in Germany and the Netherlands. Preliminary analysis of release mechanism indicates that the leaching process is complex and mainly controlled by diffusion, while signs of surface wash-off, solubility and depletion are also detected.